the PENGGUNAAN TEKNIK HIGH SPEED PHOTOGRAPHY PADA PEMOTRETAN WATER SPLASH - Wibowo, Sulistiyo; Yusuf Nurrachman; Nofiandri Setyasmara (ABEC Indonesia, 2023)
Abstract Every object, whether inanimate or living, can move or change places. Living things certainly have the ability to move themselves according to their genetics and anatomy, living things can move quickly and slowly according to their will or nature. Even inanimate objects can move if the moving object is animate or through a program mechanism and has a power source such as fuel or a battery. In the context of photography, every movement of both inanimate and living objects can be recorded according to the wishes of the photographer himself. Shutter Speed ​​(S) is a mechanism or method of image recording in which the shutter blade is lifted at a certain speed so that the light carrying the image with the help of the lens enters the film or digital sensor so that the image recording process occurs. A photographer can determine and choose the best needs in capturing moving images, either in the form of frozen images with the High Speed ​​technique where the shutter speed is relatively fast so that it can freeze fast subject movements even very fast. In this study, the author will explore the use of the High Speed ​​​​Photography technique in water media (Water Splash) by combining subjects such as fruits, vegetables and other objects combined with air in glass media so as to add artistic value to the photo shoot. As for the lighting technique, the writer will design it as ideally as possible so that the textures of objects and also water appear more attractive. Keywords: High Speed ​​photography, Water Splash, Artistic